Robot move sequence determining and multiple part-type scheduling in hybrid flexible flow shop robotic cells. (October 2016) - Batur, G. Didem; Erol, Serpil; Karasan, Oya Ekin
Highlights: We focus on the scheduling problem observed in hybrid flexible flow shops. We consider multiple part-type production in constant travel time robotic cells. The problem is first modeled as a special TSP and then a heuristic algorithm is composed. We propose a lower bound value which is valid for m -stage hybrid flow shops. Two crucial parameters affecting the performance are the load/unload and travel times. Abstract: We focus on the scheduling problem arising in hybrid flexible flow shops which repeatedly produce a set of multiple part-types and where the transportation of the parts between the machines is performed by a robot. The cycle time of the cell is affected by the robot move sequence, part/machine assignments and part sequences. In a hybrid flexible flow shop in which there exist one machine in the first and two machines in the second stage, the problem of determining the best cycle time is modeled as a traveling salesman problem. In order to provide a solution methodology for realistic problem instances, a Simulated Annealing based heuristic is constructed and the problem is solved using two different neighborhood structures. The results are also compared against an effective proposed lower bound value.